2021
DOI: 10.3892/ol.2021.12763
|View full text |Cite
|
Sign up to set email alerts
|

miR‑4417 targets lncRNA PSMG3‑AS1 to suppress cell invasion and migration in cervical squamous cell carcinoma

Abstract: Although long non-coding RNA (lncRNA) PSMG3-AS1 has been reported to participate in cancer biology, its role in cervical squamous cell carcinoma (CSCC) is unknown. The present study aimed to investigate the role of the lncRNA PSMG3-AS1 in CSCC. The expression levels of PSMG3-AS1 in both CSCC and non-tumor tissues from 64 patients with CSCC were measured by reverse transcription-quantitative PCR. The potential interaction between miR-4417 and PSMG3-AS1 was predicted using IntaRNA 2.0. Overexpression of miR-4417… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Elevated PSMG3 levels found in the plasma of glioblastoma multiforme (GBM) patients help distinguish those with sarcoidosis and healthy patients [50]. In addition, a significant number of lncRNA-PSMG3 and miRNA-PSMG3 axis regulatory mechanisms were reported to be associated with malignant diseases, including lung cancer [66][67][68][69]. On the contrary, limited literature has described the relationship between PSMG4 and human diseases, especially tumors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elevated PSMG3 levels found in the plasma of glioblastoma multiforme (GBM) patients help distinguish those with sarcoidosis and healthy patients [50]. In addition, a significant number of lncRNA-PSMG3 and miRNA-PSMG3 axis regulatory mechanisms were reported to be associated with malignant diseases, including lung cancer [66][67][68][69]. On the contrary, limited literature has described the relationship between PSMG4 and human diseases, especially tumors.…”
Section: Discussionmentioning
confidence: 99%
“…More specifically in terms of malignancies, earlier studies revealed that PSMG1 was related to increasing susceptibility to inflammatory bowel disease which can lead to colon cancer-related diseases 26 , 27 , whereas a co-expression relationship of NUP37 with PSMG1 was proposed to play a specific role in breast cancer 28 . PSMG3 is characterized as an oncogenic driver factor in various types of cancer, remarkably breast cancer and cervical squamous cell carcinoma 29 . PSMG4 variants, on the other hand, were some of the differential proteomics identified in Epstein-Barr virus-associated gastric cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, overexpression of lncRNA PSMG3-AS1 can distinguish glioblastomas from sarcoidosis and reduce the inhibitory effects of miR-34a on GBM cell proliferation ( Chen et al, 2020 ). Moreover, it has been shown that overexpression of PSMG3-AS1 could increase cervical squamous cell carcinoma cell invasion and migration, which miR-441738 inhibits ( Man et al, 2021 ). Besides, MiR-449b-5p targets lncRNA PSMG3-AS1 to suppress cancer cell proliferation in lung adenocarcinoma ( Yue et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%